Strategi Pembelajaran Innovatif: Meningkatkan Kemampuan Masalah Matematika Sekolah Dasar - Natali Theresia; Asrani Asrani (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This research aimed to improve elementary students’ mathematical problem-solving skills, which were limited by minimal teacher-student engagement and low learning outcomes (Fadli & Setiawan, 2022). To address this issue, three innovative learning models Problem Based Learning (PBL), Contextual Teaching and Learning (CTL), and Group Investigation (GI) were implemented (Rahmawati & Nurhasanah, 2021). The study employed a Classroom Action Research design using qualitative and quantitative approaches over three cycles, involving 10 fifth-grade students from SD Kristen Banjarmasin during the 2024/2025 academic year. Qualitative data were collected through observation, while quantitative data were gathered through group and individual written tests. Qualitative data were analyzed descriptively through observation results, while quantitative data were analyzed using percentage-based learning achievement criteria. Data analysis revealed significant improvements in teacher and student activities during the learning process. Students’ problem-solving skills improved progressively, and all students achieved the target mastery level (≥85%) by Cycle 3, along with improvements in cognitive, affective, and psychomotor learning outcomes. These results suggest that PBL, CTL, and GI are effective strategies for enhancing the quality of mathematics learning at the elementary school level (Putri & Hidayat, 2022).